PENGARUH LARI MALAM TERHADAP PERSENTASE LEMAK TUBUH - Supriadi, Dedi (STKIP Pasundan, 2017)
The The purpose of this study was to determine the effect of nighttime running on decreasing body fat percentage in Bandung Explorer (Bandrexhood) participants. This research is a pre-experimental design study using the one-group pretest and posttest design with instruments in the form of measurement tests, namely body fat measurements with skinfold caliper. The sample in this study were participants of the Bandung Explorer (Bandrexhood), amounting to 29 people with saturated sampling techniques. This research was conducted on May 9, 2016 data collection pretest, ended on July 1, 2016 data collection posttest. The night run is performed 24 times, 3 times a week. From the results of the t-test, the percentage of fat participants in Bandung Explorer (Bandrexhood) found that night running had a significant effect on decreasing body fat in Bandung Explorer (Bandrexhood) participants.